1995
DOI: 10.1007/bf00018884
|View full text |Cite
|
Sign up to set email alerts
|

An isolated population of fourhorn sculpins (Myoxocephalus quadricornis, family Cottidae) in a hypersaline high arctic Canadian lake

Abstract: Freshwater sculpins probably evolved from marine ancestors which entered bodies of water such as proglacial lakes or lakes which were gradually isolated from the sea by isostatic rebound . Sculpins in fresh water lakes (Myoxocephalus thompsoni [Girard]) lack cephalic horns and live well below a depth of 10 m . Those in the sea (Myoxocephalus quadricornis [Linnaeus]) typically live above 10 m and possess a well developed set of four cephalic horns . The sculpins in Garrow Lake, North West Territories, are inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…They are known to forage on both pelagic and benthic fish species [7], [10]. Cormorant populations in Greenland and Iceland are known to forage mainly on sculpins ( Myoxocephalus ) [6], [12], which are a group of cryptically coloured benthic fish with a disruptive outline pattern that may have evolved in response to avian predation pressure [13]. Given their ability to prey upon pelagic and cryptic benthic prey, and a high capacity to accommodate their eye's optical system to compensate for the loss of corneal refractive power upon immersion [3], [14]–[16], it is reasonable to expect that cormorants have a visual system well adapted to function in water and that, as in aerial predatory birds, vision is the primary sense that guides their foraging.…”
Section: Introductionmentioning
confidence: 99%
“…They are known to forage on both pelagic and benthic fish species [7], [10]. Cormorant populations in Greenland and Iceland are known to forage mainly on sculpins ( Myoxocephalus ) [6], [12], which are a group of cryptically coloured benthic fish with a disruptive outline pattern that may have evolved in response to avian predation pressure [13]. Given their ability to prey upon pelagic and cryptic benthic prey, and a high capacity to accommodate their eye's optical system to compensate for the loss of corneal refractive power upon immersion [3], [14]–[16], it is reasonable to expect that cormorants have a visual system well adapted to function in water and that, as in aerial predatory birds, vision is the primary sense that guides their foraging.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of analysed fish are shown above the bars segregation along the littoral-profundal gradient has been widely reported for salmonids (e.g. Harrod et al, 2010;Klemetsen, 2010;Muir et al, 2015) but, to the best of our knowledge, not previously reported for percids or predominantly benthivorous fishes, although some gobies and sculpins can inhabit lake profundal zones (Dickman, 1995;Ruzycki & Wurtsbaugh, 1999;Walsh et al, 2007). The pronounced differences in physical and biological properties of the different lake habitats are commonly considered as the main environmental drivers of niche specialisation within fish populations (e.g.…”
Section: Intraspecific Niche Segregation and Habitat Coupling By Ruffementioning
confidence: 81%
“…Eloranta, Knudsen, & Amundsen, ; Quevedo, Svanbäck, & Eklöv, ). However, to the best of our knowledge, no previous studies have investigated the potential of benthivorous fishes for intraspecific niche segregation along a littoral–profundal resource axis, although some predominantly littoral species of sculpins and gobies do occasionally inhabit the lake profundal zone (Dickman, ; Ruzycki & Wurtsbaugh, ; Walsh, Dittman, & O'Gorman, ). Moreover, improved understanding of how lake community and ecosystem properties affect trophic ecology of ruffe will be necessary for future monitoring and evaluation of potential impacts of this highly invasive species on recipient ecosystems (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a more recent addition to freshwater environments, invading freshwater just prior to the beginning of the Pleistocene glaciation ( Kontula and Väinölä 2003 ) after diverging from its marine sister species, the fourhorn sculpin ( Myoxocephalus quadricornis ). The most striking difference between these 2 species is the lack of cephalic horns in the deepwater sculpin, hypothesized to have been lost due to a decreased need for camouflage from aerial predators ( Dickman 1995 ). Both ciscoes and deepwater sculpin colonized many of the same postglacial lakes following the last glacial maximum ( Sheldon et al 2008 ; Turgeon et al 2016 ), but deepwater habitats are evolutionary novel ecological niches for both species.…”
Section: Introductionmentioning
confidence: 99%